EFFECT OF CURRENT SPEED ON THE APPEARANCE OF TOGOK FISHING GEAR - K. Agenti Pardosi; Nofrizal Nofrizal; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The purpose of this study is to see the appearance and performance of togok fishing gear at different current speed to predict the good current speed for processing the fishing gear’s operation. This study using the experimental method. From the result of experiments that have been done know the stronger the current speed then the stronger the reshuffle and movement of the togok fishing gear. At a current speed of 22.2 cm/sec the reshuffle and movement of the togok fishing gear seem stable. Meanwhile,at a current speed below 15 cm/sec, togok fishing gear should be taken from the waters because the flow of sea water is not strong and the catch is not maximal. Keywords: togok fishing gear,current speed, flume tank